First Parasitism Record of the Eggs of Thlastocoris laetus Mayr, 1866 (Hemiptera: Coreidae) and New Host and Distribution Records for Hadronotus vitripennis (Masner, 1983) (Hymenoptera: Scelionidae) - Oliveira, Silvana P.; Acioli, Agno N. S.; Silva, Willian M.; Pinheiro, Fábio S.; Silva, Neliton M.; Costa, Valmir A. (Entomological Communications, 2023)
Thlastocoris laetus Mayr, 1866 (Hemiptera: Coreidae) is one of the main pineapple pests in the Amazon region. A survey of the natural enemies of T. laetus in pineapples of the BRS Turiaçu variety was conducted in Manaus and Itacoatiara, Amazonas state, Brazil, revealing a parasitism rate of 28.85% of T. laetus eggs by Hadronotus vitripennis (Masner, 1983) (Hymenoptera: Scelionidae). This is the first record of parasitism in T. laetus and of the occurrence of H. vitripennis in this host in Amazonas. This natural parasitism indicates that H. vitripennis is a potential biological control agent of the pineapple bug.